Effects of Different Harvesting Practices on Forage Yield and Quality Characteristics in some Sweet Sorghum Cultivars - Elif Nur Sezgin; Fırat Alatürk (Acta Natura et Scientia)
This study was carried out to determine the above-ground and subsoil biomass production and the energy content of leaves and stalks of sweet sorghum cultivars in terms of the different harvesting heights of the crop in the research area of the Çanakkale Onsekiz Mart University Faculty of Agriculture in 2020-2021. The experiment was established according to a randomized complete block design using 4 replications, where the main plots represented the sweet sorghum cultivars (M81-E and Topper-76) while the sub-plots consisted of the harvesting heights (30 cm, 60 cm, 90 cm, 120 cm, 150 cm and the harvest at physiological maturity stage (PMS)). During the study, the experiment plots having the heights of 30 cm, 60 cm, 90 cm, 120 cm, 150 cm and PMS stage were harvested 5 times, 4 times, 3 times, 3 times, 2 times and once, respectively. Yield of fresh hay, leaf and stalk ratios, number of roots, and the values of TSBM, ME and SE of the leaves and stalks were also examined in this study. According to the results obtained, the total yields of fresh forage increased depending on the increase in plant height. In the case of the sweet sorghum (SS) cultivars, the production of fresh forage of the M81-E cultivar was higher than Topper-76. There was an increase in the ratios of stalk, while a decline was observed in the ratios of leaves depending on crop growth. On the other hand, the number of roots produced by the crops increased depending on crop growth. There was a decrease in the energy content of leaves and stalks of the crop depending on the increase in crop height during harvest. Generally, the energy contents of the leaves were found to be higher than the stalks. Consequently, sweet sorghum cultivars are to be grown in the future in terms of grazing and roughage source, and the M81-E cultivar in terms of forage yield came to be the first with a little difference. However, it was found that the Topper-76 cultivar was superior in terms of the energy content of the crop. In conclusion, it is suggested that both SS cultivars can be grown as roughage sources under similar ecological conditions.